2023
DOI: 10.1039/d2an01676a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive electrochemical platform for the p53 gene via molecular beacon-mediated circular strand displacement and terminal deoxynucleotidyl transferase-mediated signal amplification strategy

Abstract: An ultrasensitive electrochemical platform for p53 gene via MB-mediated CSD and TdT-mediated signal amplification strategy with detection limit of 0.018 fM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…2 It is reported that about 50% of the most commonly mutated genes in human cancer are wild-type p53 genes, which play a key role in cell cycle arrest, DNA repair, apoptosis, and tumor angiogenesis. 3 Moreover, the transcriptional regulation of some proteins in the human body is also related to p53 DNA. [4][5][6] p53 DNA is a veritable "genome guardian".…”
Section: Introductionmentioning
confidence: 99%
“…2 It is reported that about 50% of the most commonly mutated genes in human cancer are wild-type p53 genes, which play a key role in cell cycle arrest, DNA repair, apoptosis, and tumor angiogenesis. 3 Moreover, the transcriptional regulation of some proteins in the human body is also related to p53 DNA. [4][5][6] p53 DNA is a veritable "genome guardian".…”
Section: Introductionmentioning
confidence: 99%
“…25 We further employed a unique strategy of utilizing terminal deoxynucleotidyl transferase (TdT) to block the 3 0 hydroxyl group of DNA. 26,27 It is known that TdT is a specialized DNA polymerase enzyme that catalyzes the template-independent addition of deoxynucleotides to the 3 0 hydroxyl end of DNA strands. In our case, using TdT, we tagged dideoxyadenosine-5 0triphosphate (ddATP) to the 3 0 hydroxyl moiety of the probe/ target and thereby ensured no free hydroxyl group at this site.…”
mentioning
confidence: 99%